A tangibilidade de um serviço de manutenção de elevadores - Tomé, João Boléo (2015)
The concept of excellence service assumes an attitude and behavior that are far beyond the commitment and focus on the client, which traditionally has been practiced by many companies over the past decades. In fact, at the moment, there is a more comprehensive and wider orientation, about what it is and how the service should be done. A service, particularly a lift maintenance service, can and should be more differentiated, more tangible, more parameterized, so that we can evaluate and measure with more assertiveness. Are few, for not to say don’t exist, the studies and works devoted to this issue, so the challenge of this work was precisely that, to address a very specific matter, but with great importance for the business area. Most of the approaches to this topic tend to put more emphasize in the technical qualification of the technicians and with quality procedures compliance, forgetting the importance of interpersonal relationships between these technicians and their clients, in addition to the personal and situational characteristics, as well the importance of the maintenance planning. Having as a case study a company which carries on business in the area of elevation, were identified the various aspects that required improvement, preventive maintenance service, in order to make this service even more perceived and appreciated by the customers. For this reason, were made several customer satisfaction inquires, whose results served to define new strategies and guidelines, including that the main measure is to implement the service certification, in particular attest his main dimension which is the execution of the preventive maintenance plan, which the technicians carry out daily in many installations that have spread by its maintenance route.